Demograficzne determinanty zapotrzebowania na usługi pocztowo-telekomunikacyjne - Adamski, Eugeniusz; Karpiński, Zdzisław (Wydział Prawa i Administracji UAM, 1970)
The aim of the article is to show the connection that exists among postal and communication service and other factors that shape the numerical and qualitative level of these services. The problem was examined at the example of postal matters, subscribers and telephone calls as representatives for postal and telecommunication service and the demographic factors were chosen as the determinants. In the article there were used the statistical data of the communication year-books, the statistic year-books of the Chief Census Bureau and demographic year-book from the time of 1945 - 1966. In the first chapter there were marked unions among postal matters and density of population per square kilometre, the amount of married and not married per 1000 of people, the educational level, the amount of marriages and the migrational turn per 1000 of people. The greatest value of the coefficient factor of correlation were noted for postal matters with atternates as: married women — married men — (0.5815), density of population (+ 0.3910), higher education (+ 0.4691), divorced (+ 0.4476). In the second chapter there were matked uninos between subscribers and telephone calls and density of population per square kilometre, the amount of marriages and migrational turn per 1000 of people; people beyond the agriculture and these that worked in agriculture in percentages of the whole amount of people; the amouht of farms per 100 of people and the level of education. The greatest values of the coefficient factor of correlation were stated for telephone subscribers with such alternates as: marriages (+ 0.6598), higher education (+5379), basical education (—0.4163). With telephone calls we reached the greatest values for migrational turn (+ 0.8293), for farms (+ 0.4812), for higher education (+ 0.5770), for secondary education (+ 0.6001'), and for basical education (+ 0.4517). Therefore the demographic factors given above were accepted as granted for anticipation in the way of extrapolation.
Demographic Determinants of the Applications for Postal and Telecommunication Service